FACTORS AFFECTING FINANCIAL PERFORMANCE IN SHARIA BANKING IN INDONESIA - Marzuki; Husaini; Chairil Akhyar (CV. Radja Publika, 2024)
This study examined the factors affecting the financial performance of Islamic Banking in Indonesia. This study used secondary data taken from 11 banks. The sampling technique used was the purposive sampling technique. The method used to analyze the relationship between the independent variable and the dependent variable is the panel data regression method. The results partially concluded that Non-Performing Financing negatively and significantly influenced Financial Performance at Islamic Banking in Indonesia. The Capital Adequacy Ratio positively and significantly influenced Financial Performance at Islamic Banking in Indonesia. And the Natural Certainty Contract positively and significantly influenced the financial performance of Islamic Banking in Indonesia. Simultaneously, Non-Performing Financing, Capital Adequacy Ratio, and Natural Certainty Contract positively and significantly influenced the financial performance of Islamic Banking in Indonesia.